HAK KEKAYAAN INTELEKTUAL DALAM PERSPEKTIF HUKUM ISLAM: Kajian atas Qs. An-Nisa [5]: 29 - Wijayati, Mufliha (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
Intellectual Property Right (HKI) is now becoming an essential issue. It does not only discuss individual protection, but it has been a part of global economic and political matters. Based on Islamic law, HKI is a contemporary issue which is still problematic and invites a lot of debate in relation with its existence. Is HKI legally recognized in Islamic Sharia? Even though MUI (Indonesian Council of Ulama) has already answered with fatwa, it still important to track the issue of intellectual property right in in the perspective of Islamic law. The issue of HKI is deliberated through the study of amwal and bathil in Al-Qur’an (5: 9). The interpretation of both terms is linked with the theory of ownership and tasarrufil amwal in fiqh muamalah. This study shows that the schools of other than Hanafiyah state that HKI is a part of property ownership in the category of milk al-manfaah which must be respected. Everything that is detrimental to the owner of HKI is prohibited. The law enforcement related to HKI necessitates the involvement of government to manage it in a regulation protecting the HKI ownership.